Enhancement of Bioactivity of Natural Extracts by Non-Thermal High Hydrostatic Pressure Extraction - Scepankova, Hana (2018)
Natural extracts, likethose obtained from medicinal herbs, dietary plantsand fruitsare being recognized as important sources of bioactive compounds with several functionalities including antioxidant, anticancer, and antimicrobial activities. Plant extracts rich in phenolic antioxidants are currently being successfully used for several pharmaceutical applications and in the development of new foods(i.e.,functional foods),in order to enhance the bioactivity of the products and to replace synthetic antioxidants.The extraction method applied in the recovery of the bioactive compounds from natural materials is a key factor to enhance the bioactivity of the extracts. However, most of the extraction techniques have to employ heat, which can easily lead to heat sensitive compounds losing their biological activity, due to changes caused by temperature. Presently, high hydrostatic pressure (HHP)is being increasingly explored as a cold extraction method of bioactive compounds from natural sources.This non-thermal high hydrostatic pressure extraction (HHPE) technique allows one to reduce the extraction time and increase the extraction of natural beneficial ingredients, in terms of nutritional value and biological activities and thus enhance the bioactivity of the extracts.This review provides an updated and comprehensive overview on the extraction efficiency of HHPE for the production of natural extracts with enhanced bioactivity,based on the extraction yield,total content and individual composition of bioactive compounds, extraction selectivity, and biological activities of the different plant extracts, so far studied by extraction with this technique.